2021
DOI: 10.3389/fpsyt.2021.711734
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Specific Oxysterols and Risk of Schizophrenia in Clinical High-Risk Subjects and Patients With Schizophrenia

Abstract: Accumulating evidence from clinical, genetic, and epidemiologic studies suggest that schizophrenia might be a neuronal development disorder. While oxysterols are important factors in neurodevelopment, it is unknown whether oxysterols might be involved in development of schizophrenia. The present study investigated the relationship between tissue-specifically originated oxysterols and risk of schizophrenia. A total of 216 individuals were recruited in this study, including 76 schizophrenia patients, 39 clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“…24OHC plays a critical role in the physiological cholesterol homeostasis within the brain, and abnormal changes in 24OHC levels are associated with diseases such as Alzheimer's disease ( 32 , 33 , 34 ), amyotrophic lateral sclerosis ( 35 ), Parkinson's disease ( 14 ), and autism spectrum disorders ( 36 ). Our previous study also indicated an important role of oxysterols in schizophrenia ( 37 ). However, there have been limited studies on brain cholesterol metabolism in MDD ( 5 , 10 ).…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…24OHC plays a critical role in the physiological cholesterol homeostasis within the brain, and abnormal changes in 24OHC levels are associated with diseases such as Alzheimer's disease ( 32 , 33 , 34 ), amyotrophic lateral sclerosis ( 35 ), Parkinson's disease ( 14 ), and autism spectrum disorders ( 36 ). Our previous study also indicated an important role of oxysterols in schizophrenia ( 37 ). However, there have been limited studies on brain cholesterol metabolism in MDD ( 5 , 10 ).…”
mentioning
confidence: 65%
“…( 46 ). Plasma oxysterol levels were detected using high-performance liquid chromatography – mass spectrometry as described previously ( 37 ). In general, 50 μL of plasma or standard sample (with 5% bovine serum albumin) was mixed with 200 μL of acidic buffer solution (50 mM ammonium acetate, 1% formic acid, pH 3) and 1 mL methyl tert-butyl ether in a microcentrifuge tube, while 100 ng D5/D7 deuterium cholesterol was spiked in as an internal standard.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the metabolites cholesterol and linoleic acid (both upregulated), and L-tyrosine (downregulated), were associated with schizophrenia. Disturbed cholesterol homeostasis in the brain might increase the risk of many neurodevelopmental disorders [ 48 , 49 ], whereas the level of tyrosine, an essential amino acid, is altered in people with schizophrenia [ 50 ]. Moreover, mannitol was found upregulated on flies fed the pepper diet.…”
Section: Discussionmentioning
confidence: 99%
“…Altered oxysterol levels have been described in patients with several neurodegenerative disorders, including Alzheimer's disease, Amyotrophic Lateral Sclerosis, Parkinson's disease, and Huntington's disease [51][52][53] . While investigations into steroldysregulation in neuropsychiatric and neurodevelopmental disorders is in its infancy, changes of plasma 24S-hydroxycholesterol, a primarily neuron derived oxysterol, is found in patients with schizophrenia 54 , ASD 55 , and bipolar disorders 56 .…”
Section: Oxysterol Regulation Of Cortical Neurogenesis and Implicatio...mentioning
confidence: 99%